Analysis of Effect of GRDP (Gross Regional Domestic Product) Per Capita, Inequality Distribution Income, Unemployment and HDI (Human Development Index) on Poverty - Murbanto Sinaga (Budapest International Research and Critics University, 2020)
This study aims to examine the effect of GRDP per capita, inequality of income distribution, unemployment, and HDI on poverty. The dependent variable of the study is poverty, while the independent variable used is the GRDP per capita, income distribution inequality, unemployment, and HDI. This research was conducted in Batu Bara Regency and Medan City in the 2004-2018 period. The research data were obtained by accessing the Central Statistics Agency (BPS) website. The method of data analysis uses multiple linear regression analysis. The analysis shows that unemployment is negative and significant towards poverty. Meanwhile, per capita GRDP, income distribution inequality, and HDI have a negative and not significant effect on poverty. This study also found interesting findings, that the equality that occurred in Batu Bara Regency and Medan City was equalization in poverty not equality in welfare. Then, unemployment in Batu Bara Regency and Medan City is likely to be dominated by residents in the upper middle class who have completed Education at the senior secondary level and above.